Community Engagement, Routine Immunization, and the Polio Legacy in Northern Nigeria. (1st January 2016) - McArthur-Lloyd, Anne; McKenzie, Andrew; Findley, Sally E.; Green, Cathy; Adamu, Fatima
Abstract : Northern Nigeria has a history of low use of health services, resistance to immunization programs, and high maternal and child mortality rates. Cultural, physical, and financial barriers prevent many families from accessing health care. The Partnership for Reviving Routine Immunization in Northern Nigeria; Maternal, Newborn, and Child Health Initiative (PRRINN-MNCH) was a project funded by the UK Department of International Development and the Norwegian government that used an integrated approach to strengthen health services and increase community demand for and access to quality health care. The project's community engagement approach aimed to empower communities, work with volunteers, and develop solutions to overcome barriers to health. Simultaneously, PRRINN-MNCH was building primary health care systems, including immunization, and strengthening governance to increase the availability and quality of services. Baseline and endline population-based random household surveys conducted in 2009 and 2013 showed improved community knowledge, increased use of antenatal care and immunization services, and a decrease in maternal, infant, and under-5 mortality. In the project areas, the maternal mortality ratio fell from 1, 270 to 1, 057; under-5 mortality decreased from 160 to 90.1 per 1, 000 live births, and infant mortality decreased from 90 to 46.9 per 1, 000 live births. The overall coverage of fully immunized children rose from 2.2% to 19.3%. Many of the PRRINN-MNCH lessons learned about community engagement are relevant to the Polio Eradication Initiative when Nigeria reaches polio-free status and community mobilizers are mainstreamed into routine health services.